Gastric cancer screening: a systematic review and meta-analysis. (3rd October 2022) - Faria, Lídia; Silva, João Carlos; Rodríguez-Carrasco, Marta; Pimentel-Nunes, Pedro; Dinis-Ribeiro, Mário; Libânio, Diogo
Abstract: Background and aims: Gastric cancer (GC) screening is recommended in high-risk populations, although screening methods and intervals vary. In intermediate-risk populations, screening through esophagogastroduodenoscopy (EGD) may be considered depending on local resources. The aim of this study was to compare GC screening methods regarding effect on mortality, diagnostic yield and adherence. Methods: Systematic review and meta-analysis including studies evaluating population-based GC screening. Search was conducted in three online databases (MEDLINE, Scopus and clinicaltrials.gov), along with manual search. Results: Forty-four studies were included. Studies in upper gastrointestinal series (UGIS) demonstrated that GC screening was associated with significantly lower GC mortality rates (OR 0.63, 95% CI 0.55 − 0.73). Benefits on mortality were also found in EGD and serum pepsinogen (PG) studies. EGD was associated with significantly higher GC (0.55%, 95% CI 0.39 − 0.75%) and early-GC (EGC) detection rates (0.48%, 95% CI 0.34 − 0.65%) when compared to UGIS (GC 0.19%, 95% CI 0.10 − 0.31%; EGC 0.08%, 95% CI 0.04 − 0.13%) and PG (GC 0.10%, 95% CI 0.05 − 0.16%; EGC 0.10%, 95% CI 0.04 − 0.19%). Non-invasive methods tended to higher adherence rates when compared to EGD. Regardless of the screening method, individualized recruitment performed better. Discussion: Screening positively impacted GC mortality rates. EGD was associated with higher diagnostic yield, while UGIS and PG tended to higher adherence rates. Screening uptake was predominantly impacted by recruitment strategies independently of the adopted method.